ANALISIS PENGARUH MUSIM KEMARAU TERHADAP JASA LINGKUNGAN AIR TUK JIRAK DI WILAYAH RESORT WONOLELO, TAMAN NASIONAL GUNUNG MERBABU - Ahsan Risfathoni Almadani; Wahyu Gilang Hermawan (Nusantara Hasana Journal, 2023)
“Tuk” is another name for spring water which is the emergence of groundwater to the ground surface and can also be through seepage in rocks. The use of this spring is very diverse, including as drinking water needs, agricultural irrigation and daily needs. The management of the area around the spring has a significant impact on the discharge and quality of the water produced, such as the influence of the amount of vegetation which is one of the main factors affecting the size of the water discharge produced. The results showed that environmental conditions, community knowledge and local culture will greatly affect the management of springs which in this case there must be participation in the role of technology so that optimal benefits and continuity of function of springs are obtained. The purpose of this study is to determine the condition and utilization of Tuk Jirak water environmental services as the main water source for the community in Glondong Duwur Village and Blumbang Village and their influence during the dry season.